(untitled) (Research, Society and Development, 2020)
The use of renewable sources has grown worldwide and in Brazil the incentive to use wind energy has been significantly expanded. The country’s largest wind potential is concentrated in the Northeast (NE). The objective of this work is to measure the degree of regularity or predictability of wind velocity over Brazilian NE through the Sample Entropy method. The analyzes were carried out from the historical series of the ERA-40 reanalysis, arranged on a world grid with spatial resolution of 2,5° x 2,5° in records made at 10 m from the ground during the 00, 06, 12 and 18h during the period from 1957 to 2001. In addition to the four synoptic hours, daily, monthly and seasonal series were also generated. The results showed that the regions with higher wind speeds also present better predictability for the series. In addition, indicate that different areas with similar wind speed averages may have different predictability.